2006
DOI: 10.1097/01.brs.0000238675.91612.2f
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure During Pedicle Screw Placement in Adolescent Idiopathic Scoliosis: Is Fluoroscopy Safe?

Abstract: The spinal surgeon's intraoperative radiation exposure may be unacceptable. Spinal surgeons should be considered classified workers and monitored accordingly. Methods to lower radiation dosage seem strongly indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(70 citation statements)
references
References 13 publications
1
67
0
2
Order By: Relevance
“…Fewer pedicle screws have been shown to result in a shorter operative time and decreased radiation if intraoperative fluoroscopy is used. 52 The minimum screw density pattern reduces the operative time (mean 145 minutes vs 177 minutes for 10-level fusion) required for screw placement. 12,22 Shorter operative time may conceivably decrease the rate of infections and other medical complications.…”
Section: Limitations Of the Medical Modelmentioning
confidence: 99%
“…Fewer pedicle screws have been shown to result in a shorter operative time and decreased radiation if intraoperative fluoroscopy is used. 52 The minimum screw density pattern reduces the operative time (mean 145 minutes vs 177 minutes for 10-level fusion) required for screw placement. 12,22 Shorter operative time may conceivably decrease the rate of infections and other medical complications.…”
Section: Limitations Of the Medical Modelmentioning
confidence: 99%
“…28,29 Fluoroscopic techniques have been reported to have relatively high false-negative rates. 30 A study by Ul Haque et al 20 on radiation exposure with all screw constructs in adolescent idiopathic scoliosis showed that a nonclassified radiation worker (i.e. the surgeon) inserting approximately 2,800 screws under fluoroscopic guidance is projected to receive 13.49 mSv of whole body ionizing radiation and 4.31 mSv of thyroid gland irradiation annually.…”
Section: Descriptores: Fluoroscopía Tornillos óSeos; Columna Vertebrmentioning
confidence: 99%
“…This technique results in the least radiation exposure to the patient and surgeon but is less accurate in placing contained pedicle screws as compared to imaging techniques. 18 A fluoroscopic technique may provide more consistent results but carries some risks associated with radiation dose, especially to young patients 19,20 and to the surgeon. 20 This manual PediGuard technique most closely matches the freehand manual technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spinal surgery, high doses of ionizing radiation are delivered during surgical procedures that require fluoroscopic control, such as correction of spinal deformities with third generation transpedicular screws or kyphoplasty (12,17). Therefore, radiation safety has become a major concern for spinal surgeons in recent years.…”
Section: Introductionmentioning
confidence: 99%